A critical review of the assessment of medical gloves. (2nd January 2021) - Preece, D.; Lewis, R.; Carré, M. J.
ABSTRACT: Medical protective gloves must be assessed to adequate standards before becoming available for commercial use. Strength, integrity and contamination are assessed at the manufacturing stage. However, concerns are raised over the standardisation of the testing; should more be done to assess how gloves affect the performance? Over the years, studies have demonstrated how the design of gloves has reduced tactile sensitivity in medical staff, ultimately leading to poor patient care through missed information. Studies have also demonstrated that a loss of grip control and dexterity through glove use are detrimental to medical tasks. However, it remains relatively unexplored as to how wearing medical gloves affects the users and the patients. Gaps in research have been identified around the frictional and grip properties of gloves. Linking the key performance parameters to the manufacturing processes, which affect material properties, will provide more insight into the behaviour of medical gloves and how to properly assess materials.